The Strategy for Implementing Agricultural Extension Based on Cyber Extension in Malang Raya Region, Indonesia - Sabir Sabir; Sugiyanto Sugiyanto; Keppi Sukesi; Yayuk Yuliati (HABITAT, 2019)
This study aimed to formulate a strategy for implementing agricultural extension based on cyber extension in Malang Raya region. This research was conducted in Malang raya region using purposive sampling technique. The analysis used to determine strategy priority for implementing agricultural extension used SWOT analysis. Based on internal analysis (IFAS) and external analysis (EFAS) implied that the position of cyber extension utilization by agricultural extension workers in the Malang Raya Region was in the area of strategy I, namely Aggressive Strategy. This depicted that the strength possessed can take advantage of opportunities and improve weaknesses optimally, so the determination of the strategy for optimizing the use of cyber extensions was more directed at aggressive strategies. Based on this study showed that the measures should be implemented such as the implementation of legislation has the greatest contribution, optimization of the utilization of information technology devices, optimization of utilization of the agricultural extension centre in each sub-district, and increasing competency and the professionalism of administrators in accordance with their respective duties and authorities.